Improvement in verbal memory performance in depressed in-patients after treatment with electroconvulsive therapy - Biedermann, Sarah Violetta; Ende, Gabriele; Sartorius, Alexander (Acta psychiatrica Scandinavica, 2016)
Objective Electroconvulsive therapy (ECT) is a highly effective and well-tolerated therapy for severe and treatment-resistant depression. Cognitive side-effects are still feared by some patients and clinicians. Importantly, cognitive impairments are among the most disabling symptoms of depression itself. Methods Patients suffering from a severe episode of depression were treated with either ECT or treatment as usual (TAU) in an in-patient setting. Matched healthy participants served as controls (HC). Verbal memory was tested with the California Verbal Learning Test (CVLT) before the specific treatment started (ECT = 15, TAU = 16, HC = 31) and 2 months after the last ECT session or 2 months after discharge respectively. Results Before the specific treatment started, depressed patients performed substantially worse compared with HC in total, short- and long-delay recall in the CVLT, while the ECT group showed the worst performance. More severely depressed patients showed worse performances in these measures. Intriguingly, verbal memory showed a significant improvement in ECT-treated patients, but not in the other groups. No differences between the groups were found at follow-up. Conclusion Contrary to the widely feared assumption that ECT has long-term impact on memory functions, we found evidence that ECT is superior to TAU in improving verbal memory in depressed patients.